KAWASAN BERPOTENSI BANJIR PADA DAERAH ALIRAN SUNGAI (DAS) KURANJI - Utama, Lusi (Rang Teknik Journal, 2022)
The extreme climate from 2012 resulted in high rainfall. Watershed damage from research on Kuranji describes the Batang Kuranji watershed in a damaged state. Watershed (DAS) is an ecosystem unit where living bodies and their environment interact, interdependence on their constituent components. Batang Kuranji has a river flow with a main river length of 32.41 km which crosses 5 SUB-DAS, namely Sungkai, Padang Janiah-karuah , Belimbing, Batang Kuranji and Danau Limau Manih. The upstream of the Kuranji watershed is the Bukit Barisan mountain range with an area of 202.7 km2 of the Kuranji watershed, with an average maximum annual rainfall of 3,500 mm. By using the Thiessen method from 3 rainfall stations from 2012 to 2020, the planned rainfall is obtained. From the image map with the ARC GIS program, we get a watershed map, a map of rainfall stations and a map of land use. From the analysis of discharge rationally, the discharge due to land use for green areas that can store water in forests and plantations for the Danau Limau Manih SUB-watershed is 15.82 m3/second, for the Danau Limau Manih SUB-watershed area, the green area is 6.46 m3/second, for the Batang Kuranji sub-watershed, the discharge due to the green area is 2.52 m3/second, which is small from the discharge due to residential land use. From these 3 SUB-watersheds, it is necessary to arrange land use.Keywords: extreme, rainfall, land use, watershed